The use of English derivational forms by Malaysian ESL learners - Md Enzai, Ida Malina; Mohammad Lotfie, Maskanah (2015)
This study presents an investigation on the production of English derivational forms by Malaysian secondary school students. Although the use of the forms has been the subject of study in numerous ESL settings, the same cannot generally be said in the Malaysian context. Being one of the main sources for English vocabulary, derivational morphological process is an essential yet complex and confusing aspect of English language learning. ESL learners struggle in their effort to become competent English language users because their success is partly dependent on and reflected by their use of derivational forms. In this study, a comprehensive analysis conducted on derivatives produced in ninety essays has identified the types of derivations used by the learners. Neutral and non-neutral affixes underlie the classifications of the derived forms. The findings, which come with theoretical and pedagogical implications, indicate that neutral affixes are more prevalently used. More accurately formed words with neutral affixes have been identified. This study also provides a new insight into the use of adverbial affixes whereby these specific affixes have been considered as one of the less commonly used forms by English language users. There is evidence that the written output of the learners who were involved in this study who came from different levels of English language proficiency contains considerable usage of adverbial derivatives.